Auditoria operativa al componente del talento humano en la compañía Agrosemilla s.a del cantón Mocache - Marcillo Rendon, Ligia Maria (2012)
The review of audit operations for the talent in the company Agrosemilla S.A., province the rivers during the period 2010, to establish improvement opportunities and achieve the business mission has developed. For the present we applied research techniques such as observation and analysis of documents, through which you could collect information necessary for the audit. Instruments were used for the analysis of such information as the implementation of internal control and process map questionnaires. In addition to the first two chapters, bibliographic, technological and graphical methods were used. Also carried out a program of audit, where procedures were established to measure the operations of the company, to determine findings and solutions to the problems found with the help of various research techniques, step by step was carried out collecting relevant information. The proposal for the examination of performance audit to the macroprocesos to the human talent in the company Agrosemilla S.A., is to evaluate the business mission which relies in seeking the satisfaction of customers since they are the cornerstone of any company, which focused on evaluate the technician of the company, taking into account that performs the basic operations of the company. Therefore, it is recommended to pay attention to such findings so that in the future these not caused an impact in their operations, which are in the audit report issued.